Respon Fisiologis Dan Psikologis Saat Terjadi Halusinasi Dengar Pada Pasien Skizofrenia Paranoid Di Rumah Sakit Jiwa Daerah Soedjarwadi Klaten - Rahmadani, Wilda; , Arum Pratiwi, S.Kp., M.Kes (2017)
Introduction the physiological and psychological responses when auditory hallucination accurs in the paranoid scizoprenia patients have different responses between an individual and another because the responses are inflluenced by the individual in responding the hallucination and mechanism of coping user by the individual him or herself. This research aims to obtain the chracteristic description of physiological and psychological responses that occur in the patients when the auditory hallucination occurs in the paranoid schizoprenia patients. The method of research used is qualitative through a physiological narrative approach. The number of respondents participated in this research is b people who were selected using a consideration that the repondents could give information when a semi structure interview was conducted using a voice recording device. The results of research obtained by the researcher in this research are that the responses occur in the pateients are different such as the sensation of pulse beat, rapid breathing, anxiety, being worried on what they heard, fear, uncasy feeling, and sad feeling, Meanwhile, the behavioral patterns showed by the individuals have similarities such as being strained, restless behavior,being noisy, being uneasy, moving back and forth, laughing, talking to him or herself, unfocused eye contact,easy to turn attention when doing communication, vesible tremor and sweat. Limitation in this research, the researc did not use technique of discussin group focus because of the time limitation in the research. Conclusion the physiological responses when auditory hallucination occur in the paranoid schizoprenia patients in Rumah Sakit Jiwa (mental hospital) Soedjerwadi Klaten are varied among individuals. The responses they underwent, among others, are : rapid breathing, sweat, sensation of pulse beat, being wary, strained, yhe client focussed on the voice they heard, and a motor agitation occured,meanwhile, the psyhological responses underwent when the auditory hallucination occurs in the schizoprenia patients in the mental hospital soedjarwadi klaten are varied such as suspicion, anxiety accompanied by sadness, restless, being noisy, and uneasy feeling. Suggestions for the medical employees, they should be albe to know specifically the physiological and psychological responses in the paranoid schizoprenia patiets who undergo hallucination, therefore,they can give a proper therapy,so, it can prevent the patients from being absorbed in the hallucination they undergo, and for the future researchers, a furtherreseaech should be conducted and the area of research should be broadened, therefore, it can obtained various and specific information. Keywords : physiological response, psychological response, auditoty hallucination, paranoid schizoprenia.